Effect of medical innovation policies on the prevention and control of the COVID-19 and the impact of the “Belt and Road” economy - Chen, Yirun; Zhao, Zichao; Dai, Wensheng (Frontiers in Public Health, 2022)
With the spread of the COVID-19, it is urgent for everyone to protect themselves. The introduction of the medical innovation policy has also brought certain effects to the prevention and control of the COVID-19. The specific effect will be reflected in the following research. This paper firstly analyzed research results related to medical innovation policy, COVID-19 prevention and control, and the "One Belt, One Road" economy, finding out the content that fits this research, and innovates the research work on this basis. Then, this paper provided a detailed explanation of medical innovation policies, the prevention and control of the COVID-19, and the "One Belt, One Road" economy. Among them, this paper focuses on the "One Belt and One Road", uses the α-convergence model to analyze the economic changes of the "One Belt and One Road", and conducts experimental tests in the medical field. The results have shown that from 2017 to 2019, the average hospitalization expenses paid by the pooled funds were 4986.19 yuan, 4997.34 yuan, and 4888.60 yuan, respectively.